(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Michelle Good is a Cree writer and a member of the Red Pheasant Cree Nation in Saskatchewan. After working for Indigenous organizations for twenty-five years, she obtained a law degree and advocated for residential school survivors for over fourteen years. Good took up master’s in creative writing from the University of British Columbia. Her poems, short stories, and essays have been published in magazines and anthologies across Canada. As a lawyer, she has been a tireless promoter for Indigenous people specially the survivors of residential schools. Five Little Indians by Michelle Good is the story of five Indigenous people, all who attended residential school in British Columbia. The book focuses on the aftermath of school life, demonstrating how the children’s lives are affected by the abuse they have gone through while in school. The novel exposes the compelling and devastating ugly Canadian truth-harsh treatment of school children, yet it a beautiful work of literary art. The teens’ struggle for survival can be witnesses in the novel Five Little Indians which is a fictional look at the real Canadian legacy of residential schools